Comparison of Oil Transmissivity Methods Using Bail‐Down Test Data. Issue 3 (6th September 2016) - Palmier, Cédric; Dodt, Matthew; Atteia, Olivier
Abstract: This paper evaluates the results from three methods commonly used to estimate oil transmissivity: the modified Cooper solution (Beckett and Lyverse 2002), the modified Bouwer and Rice method (Kirkman 2013), and the modified Jacob and Lohman method (Huntley 2000). Determining the validity of oil transmissivity values is important (e.g., when used in extraction system design and operation) and not straightforward as these methods are based on different assumptions and boundary conditions and introduce different simplifying assumptions to allow for estimating oil drawdown. Data from 289 bail‐down tests performed during an oil remediation project were used in this evaluation. Analysis of these tests produced realistic transmissivity values and good correlation between these three methods, giving the authors confidence in the oil transmissivity values as this correlation is reflected across a significant number of data sets. Secondly, the nature of oil and water recharge to the wells interpreted from Kirkman's J‐ratio values largely validates the Huntley (2000) simplifying assumption that the potentiometric surface will be relatively constant during the test, allowing the use of the modified Bouwer and Rice method. Finally, the impact of oil extraction on measured oil thickness and estimated oil transmissivity was also assessed. The study showed a clear general decrease in both measured oil thicknesses and estimated oil transmissivity during the oil recovery project. However, measured oil thickness and estimated oil transmissivity are not clearly correlated, and, as a consequence, the range of decrease in one parameter does not allow any prediction of the range of decrease in the second parameter.